Evaluation of Salivary and Serum Antioxidant and Oxidative Stress Statuses in Patients with Chronic Periodontitis: A Case-Control Study - Ahmadi-Motamayel, Fatemeh; Goodarzi, Mohammad T.; Jamshidi, Zohreh; Kebriaei, Reza (Frontiers in Physiology, 2017)
AAim: In periodontitis local bacteria stimulate polymorphonuclear neutrophils to release reactive oxygen species. Increased levels of oxidative stress play main role in the periodontitis pathogenesis. So this study aimed to evaluate salivary and serum total antioxidant capacity and malondialdehyde in patients with chronic periodontitis. Material and Methods: Fifty-fivehealthy person and 55 patients with chronic periodontitis with 30-50 years' age range were participated. After clinical examination and case selection, unstimulated whole saliva was collected at the morning. Blood samples took from the antecubital vein. Total antioxidant capacity and malondialdehyde level were evaluated by spectrophotometric assay. Data were analyzed using Stata.11 software with t-test. Results: Periodontitis group had lower salivary 0.16 and serum 0.36 total antioxidant capacity.( p=0.11) than that of control group. Mean salivary malondialdehyde level in case and control group was 0.80±0.09 and 0.42±0.08 respectively. The results showed significantly higher level of salivary and serum malondialdehyde in periodontitis group. Gender did not have any effect on antioxidant and oxidative stress level. Conclusion: This study indicated increased level of salivary and serum oxidative stress in patients with chronic periodontitis. Total antioxidantcapacity was mildly lower in the saliva and serum of these patients. Higher malondialdehyde with no change in antioxidant status can cause systemic and local complications in these patients.